Strategi Dinas Pendapatan Daerah Dalam Meningkatkan Retribusi Pajak Perhotelan Di Kota Ternate - Wangko, Lukman; Yuliana, Yuliana (Peneliti.net, 2024)
Strategy of the Regional Revenue Service in Increasing Hotel Tax Levy in Ternate CityIt should be noted that the existence of taxes causes two situations to change. First, the reduced ability of individuals to control resources for the benefit of controlling goods and services. Second, the increase in the state's financial capacity in providing public goods and services that are the needs of the community. So the main problem in this study is How is the Strategy of the Regional Revenue Service in Increasing Hotel Tax Levy in Ternate City. And this study aims to understand how the Strategy of the Regional Revenue Service in Increasing Hotel Tax Levy in Ternate City. This type of research is Descriptive Qualitative, in order to obtain a clear picture of the Strategy of the Regional Revenue Service in Increasing Hotel Tax Retribution in Ternate City. While the data collection techniques used are interview techniques, observation and documentation techniques. In the data sources obtained in this study, the author collected through several informants, namely the Head of the Regional Revenue Service, one Head of Revenue Division, one Head of Collection Section, and three hotel entrepreneurs. So, the total number of informants is six people. Furthermore, the literature review discusses the concept of strategy, the concept of regional income, the concept of regional retribution, the concept of hotel tax. This study shows that the strategy implemented by the agency is to use three methods, namely Extervication, which is a method related to the expansion of the agency's work area. Intensification, which is related to improvements in the field of collection, then Destervication, which is related to the search for new objects. Then the obstacles faced in the field are internal obstacles, namely obstacles caused by the agency itself. While external obstacles are obstacles caused by outsiders. Hotel tax payments are made at the Regional Treasury or other places designated by the Regional Head according to the specified time. If tax payments are made at other designated places, the results of tax receipts must be deposited into the Regional Treasury no later than 1 x 24 hours or within a time specified by the Regional Head. Tax payments as referred to above are made using Proof of Payment (TBP”). Some research results in the field, that the Ternate City Government in order to increase hotel tax levies in order to increase the regional income budget, which leads to the welfare of the people in Ternate City. However, the reality in the field shows that the government only thinks about how hotel entrepreneurs can deposit taxes into the regional treasury but the government does not think about how to promote its region in order to attract tourists.